2022
DOI: 10.1007/s00299-022-02838-1
|View full text |Cite
|
Sign up to set email alerts
|

Arabidopsis CPR5 plays a role in regulating nucleocytoplasmic transport of mRNAs in ethylene signaling pathway

Abstract: The ETR1 receptor plays a predominant role in ethylene signaling in Arabidopsis thaliana. Previous studies showed that both RTE1 and CPR5 can directly bind to the ETR1 receptor and regulate ethylene signaling. RTE1 was suggested to promote the ETR1 receptor signaling by in uencing its conformation, but little is known about the regulatory mechanism of CPR5 in ethylene signaling. In this study, we presented data showing that both RTE1 and CPR5 bound to the N-terminal domains of ETR1, and regulated ethylene sign… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 81 publications
0
8
0
Order By: Relevance
“…Ethylene plays a key role in melon sex determination through signal transduction processes. CPR5 has been proven to be a key gene in the ethylene signal transduction pathway, where it promotes ethylene signal transduction by directly binding to ETR1 (ethylene receptor protein). , We hypothesized that the ethylene signaling pathway mediated by CmCPR5 mutation in Y101 was dysfunctional. Since using ethephon solution is a common method of investigating the response of sex-determination-related genes to ethylene in Cucumis, , we investigated the expression pattern of CmCPR5 under different ethephon treatments, according to previous studies. , …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Ethylene plays a key role in melon sex determination through signal transduction processes. CPR5 has been proven to be a key gene in the ethylene signal transduction pathway, where it promotes ethylene signal transduction by directly binding to ETR1 (ethylene receptor protein). , We hypothesized that the ethylene signaling pathway mediated by CmCPR5 mutation in Y101 was dysfunctional. Since using ethephon solution is a common method of investigating the response of sex-determination-related genes to ethylene in Cucumis, , we investigated the expression pattern of CmCPR5 under different ethephon treatments, according to previous studies. , …”
Section: Resultsmentioning
confidence: 99%
“…4 was found to encode CPR5 protein, which is a multipotent enzyme involved in many plant growth and development processes and disease regulation pathways. Notably, CPR5 responds to ethylene, and recently, AtCPR5 has been shown to regulate ethylene signaling in A. thaliana by interacting with the ethylene receptor AtETR1 . , Based on this, we analyzed the expression of CmCPR5 (Candidate No. 4, MELO3C007802) and found that the expression was suppressed in the bisexual line Y101 but induced in the unisexual line 0426 by ethylene in a dose-dependent manner.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The involvement of CPR5 with plant disease defense had been deeply studied in Arabidopsis . The study showed that CPR5 played important roles in signaling pathways, such as CKI-RB-E2F cell cycle signaling pathway, activated immune responses, and ROS signal transduction ( Borghi et al, 2011 ; Chen et al, 2022 ). CPR5 was also found to be involved with multiple plant hormones signaling pathways, such as salicylic acid and ethylene ( Clarke et al, 2004 ).…”
Section: Introductionmentioning
confidence: 99%